Muscle weakness as an additional criterion for grading sarcopenia‐related prognosis in patients with cancer. (10th December 2021) - Cereda, Emanuele; Tancredi, Richard; Klersy, Catherine; Lobascio, Federica; Crotti, Silvia; Masi, Sara; Cappello, Silvia; Stobäus, Nicole; Tank, Maja; Cutti, Sara; Arcaini, Luca; Bonzano, Elisabetta; et al.
Abstract: Background: Low muscle strength has been pointed out as a key characteristic of sarcopenia, but the prognostic significance of muscle function next to reduced skeletal muscle mass (SMM) in patients with cancer has been scantily investigated. Methods: Data on muscle strength by handgrip (HG) dynamometry and total‐body SMM estimated by bioelectrical impedance analysis (BIA) of Italian and German patients with cancer observed prospectively until death or censoring were analysed ( N  = 1076). Patients were stratified in four risk categories based on low HG (<10th percentiles of age and gender‐specific normative values) and low total‐body SMM according to SMM index cutoffs (<10.75 and <6.75 kg/m 2 in men and women, respectively). Results: During a median follow‐up of 58 months [25th–75th percentile, 37–60], 566 patients had died. Patients presenting low HG in combination or not with low SMM were characterised by shorter median survival (12.7 vs. 27.2 months, respectively; p  < 0.001) compared to those with low SMM/normal HG and normal SMM/normal HG (>60 months for both). After adjusting for sex, age, body mass index and percentage of weight loss, disease's stage, performance status and type of cancer, compared to reference category (normal HG and SMM; N  = 210) the hazard ratios were: low SMM/normal HG ( N  = 342), 0.83 [95% confidence interval, CI, 0.67–1.02] ( p  = 0.073); normal SMM/low HG ( N  = 158), 1.19 [95% CI, 1.07–1.32] ( p  = 0.002); low SMM/low HG ( N  = 366), 1.39 [95% CI, 1.27–1.53] ( p  < 0.001). Conclusions: Muscle weakness was found to be a more powerful predictor of survival than BIA‐estimated SMM and should be considered as an additional key feature of sarcopenia in patients with cancer. Abstract : Low muscle strength has been pointed out as a key characteristic of sarcopenia, but the prognostic significance of muscle function next to reduced skeletal muscle mass (SMM) in patients with cancer has been scantily investigated. Muscle weakness was found to be a more powerful predictor of survival than SMM and should be considered as additional key feature of sarcopenia in patients with cancer.